Control strategies for atmospheric pressure plasma polymerization of fluorinated silane thin films with antiadhesive properties. Issue 4 (27th December 2022) - Laghi, Giulia; Franco, Domenico; Condorelli, Guglielmo Guido; Gallerani, Riccardo; Guglielmino, Salvatore; Laurita, Romolo; Morganti, Dario; Traina, Francesco; Conoci, Sabrina; Gherardi, Matteo
Abstract: Finding proper strategies to control plasma polymerization processes is a crucial aspect to produce thin films with tailored characteristics. In this work, the validity of the Yasuda parameter W/FM (W: discharge power and FM: precursor feed rate) as a controlling parameter for a polymerization process assisted by an atmospheric pressure single electrode plasma jet and the aerosolized fluorinated silane precursor trimethoxy(3, 3, 3‐trifluoropropyl)silane is demonstrated. The properties of thin films deposited under different W/FM values are discussed using attenuated total reflectance—Fourier transform infrared (ATR‐FTIR) spectroscopy, X‐ray photoelectron spectroscopy (XPS), water contact angle (WCA) measurements, and scanning electron microscopy (SEM). Results suggest the presence of two deposition domains as a function of W/FM (an energy‐deficient domain and a monomer‐deficient domain), each inducing coatings with different chemical and physical properties. Furthermore, coatings deposited under the same W/FM values exhibit similar characteristics regardless of the power and feed rate values adopted. Considering the potential use of the deposited coatings to increase the antiadhesive properties of implantable medical devices, preliminary results on coatings' antiadhesive activity against Pseudomonas aeruginosa and Staphylococcus aureus are presented. Abstract : Finding proper strategies to control plasma polymerization processes is a crucial aspect to produce thin films with tailored characteristics. In this work, the validity of the Yasuda parameter (W/FM, W: discharge power and FM: precursor feed rate) as a controlling parameter for a polymerization process assisted by an atmospheric pressure single electrode plasma jet and an aerosolized fluorinated silane precursor is demonstrated. Coatings deposited under different W/FM values are characterized using attenuated total reflectance—Fourier transform infrared spectroscopy, X‐ray photoelectron spectroscopy, water contact angle measurements, and scanning electron microscopy analyses. Considering the potential use of fluorine‐containing coatings in the biomedical field, preliminary results on coatings' antiadhesive activity are presented.